Christianity: A Phenomenological Approach? - Michel Henry (Journal of French and Francophone Philosophy, 2018)
Here I investigate the possibility of a phenomenological approach to Christianity, with the understanding that this would not be a matter of proposing an interpretation, but that such an “approach” would be able to lead directly to the heart of Christianity. I will say immediately that a phenomenology that would be able to undertake such a task is not the historical phenomenology that was born with Husserl. Only an ideal phenomenology that would become what is required would be able to respond to our investigation. This ideal phenomenology is a phenomenology of life.